Invisible subjects in clinical research: intersectionality and legal strategies for inclusion (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The under-representation of women, older people and ethnic minorities in clinical trials of drugs and medical devices has the potential to significantly impact the health protection of these clinical populations. Adopting an intersectional perspective, the article first reconstructs the causes of this phenomenon and illustrates its serious consequences, and then proposes the identification of (de iure condito and de iure condendo) legal solutions that could facilitate the circulation of more inclusive trial protocols.
Keywords: Clinical trials; exclusion; patient protection; intersectionality; civil liability; responsabilità civile